The Use of Round Table Method to Improve Student’s In Speaking Skill at Seventh Grade Students of Senior High School - Sisman Nuriadi; Ahmad Zuhri Rosyidi; Zihori Maulida (JURNAL ASIMILASI PENDIDIKAN, 2025)
The Purpose of this research is to determine the impact of the Round Table method on improving students' speaking skills at first grade students of SMPN SATAP 3 Pringgabaya. In this research, researcher used Classroom Action Research by Kemmis and MC Taggart as the research design. This research was carried out in one cycles, this cycle consisting of planning, implementation, observation and reflection. Data collection was carried out by observation and tests. Data were analysed using quantitative and qualitative analysis. The research results show that the application of the Round Table Method can improve students' speaking abilities. This is proven by student achievement through the Minimum Completion Criteria (MMC) (?70) with a success indicator (70%) In this cycle results where 95% of students achieved a score of 70 or higher, while only 5% scored below 70. The highest post-test score was 92, and the lowest was 60, with an average score of 80.32. The percentage increase in students from post-test was 33%. This learning method also improves students' attitudes/activities at every meeting during the learning process. Thus, it can be concluded that the Round Table Method can improve the speaking skills of first grade students at SMPN SATAP 3 Pringgabaya.